2011
DOI: 10.1590/s0102-311x2011000800016
|View full text |Cite
|
Sign up to set email alerts
|

Consumo de álcool entre estudantes universitários

Abstract: Consumption of alcoholic beverages is widely encouraged by the mass media, despite the related health risks. Today's students in the health fields are the professionals of tomorrow who will be providing advice and serving as role models for patients. The aim of this study was to analyze alcohol consumption and related factors among these students. A total of 608 male and female university students from Maceió, the capital of Alagoas State, Brazil, completed a self-administered questionnaire. Data analysis incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
34
0
91

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(137 citation statements)
references
References 23 publications
6
34
0
91
Order By: Relevance
“…That the places of use most frequently reported by the first and fourth year students were university parties is in agreement with the reports of previous studies 7,15 . In a study published by Andersson et al 16 , students claimed that the use of alcohol made their parties livelier.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…That the places of use most frequently reported by the first and fourth year students were university parties is in agreement with the reports of previous studies 7,15 . In a study published by Andersson et al 16 , students claimed that the use of alcohol made their parties livelier.…”
Section: Discussionsupporting
confidence: 93%
“…Carvalho et al 7 , based on the results of a study conducted with students of three health courses in the state of São Paulo, found that the situations in which the students consumed more drugs were related to the university environment. Chiapetti and Serbena 8 who studied students of the medical school of Paulista State University (UNESP) also noted the great influence exercised by university life regarding drug use on the part of students.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies with female university students also detected early ages for experimenting alcoholic drinks 5,14,24,25 as well as a positive correlation between binge drinking and the start of alcohol use before entering higher education. 25 Research carried out among female university students from the south of the country found that more than 90% of those who consumed alcoholic beverages, started drinking before entering university.…”
Section: Discussionmentioning
confidence: 78%
“…This was similar to the rates observed among students of health area in the State University of Montes Claros, MG (74.9%), 4 among students aged 13 to 17 years in public schools in Uberlândia, MG (80.9%) 22 and in Mexican medical students aged 17 to 25 years (71.9%). 5 Prevalences of approximately 90% were found for alcohol use in the lives of university students in 27 Brazilian state capitals, 23 in students of health sciences colleges in Maceió, Alagoas, 24 and among medical students from the state of Minas Gerais. 25 These data show the high consumption of alcohol among young students of both sexes, including university students of health sciences area.…”
Section: Discussionmentioning
confidence: 99%
“…O aumento desse consumo nessa população tem gerado preocupações nos estudiosos da área e, em decorrência disto, estudos têm avaliado o padrão deste consumo, assim como intervenções preventivas efi cazes que o diminuam (Lorant et al, 2013;Pedrosa, Camacho, Lambert, & Oliveira, 2011;Ramis et al, 2012;Wagner et al, 2012).…”
Section: Segundo Dados Do I Levantamento Nacional Sobre O Uso De áLcounclassified